Misconceptions Towards Department of Education Advisory: A Challenge in the Philippine Education System - Mark Gabriel Aguilar; Hasibul Islam (Educational Challenges)
To ensure teachers can provide quality education, it is essential to continuously enhance their knowledge and skills through professional development opportunities, including seminars and training programs. However, ensuring that teachers only attend quality professional development events is critical to preventing incompetence and promoting actual learning. In the Philippines, the Department of Education (DepEd) provides information about professional development opportunities through DepEd Advisories. Unfortunately, many educators misconstrue these as endorsements for events, publications, and other opportunities, although it is just information dissemination, leading to their vulnerability to predatory practices and the exploitation of the document. Issuance of a DepEd Advisory does not necessarily assure the legitimacy of an event or opportunity, and because of this, educators may invest in activities that are not beneficial to their students or careers.